Pelatihan Pembuatan Makanan Bergizi Seimbang untuk Meningkatkan Sistem Imun - Romadhiyana Kisno Saputri; Akhmad Albari (IKIP PGRI Bojonegoro, 2021)
Total confirmed cases of COVID-19 in Bojonegoro until June 15, 2020, positive patients were 84 people with 12 cases died (CFR 14.28%). The death rate due to COVID-19 in Bojonegoro is relatively high, so it is necessary to hold several activities to fight COVID-19 in Bojonegoro, one of which is maintaining the personal immune system. Increasing immunity can be done by consuming food with balanced nutrition. This form of community service activity is to increase the capacity of the community with a type of education program and training in making food with balanced nutrition. The partner in this community service program is the head of the PKK. The participation of the PKK chairman includes granting activity permits and gathering the community for community service activities. The schedule for the implementation of the activity is for three months, August-October 2020. This activity went well, there was an increase in the knowledge and skills of respondents about making food with balanced nutrition to improve the immune system. 87.5% of respondents have good knowledge about balanced nutrition, 100% of respondents can make food with balanced nutrition and 93.75% of respondents have implemented balanced nutrition in the food consumed every day. Suggestions for this community service activity include adding days of mentoring so as to ensure that if a habit has been formed in serving nutritionally balanced meals and adding or expanding targets because currently it is very important to serve balanced nutritious food. Total kasus konfirmasi COVID-19 di Kabupaten Bojonegoro, sampai 15 Juni 2020, pasien positif 84 orang dengan 12 kasus meninggal (CFR 14,28%). Angka kematian karena COVID-19 di Bojonegoro tergolong tinggi, untuk itu perlu diadakan beberapa kegiatan untuk melawan COVID-19 di Bojonegoro, salah satunya menjaga sistem imunitas diri. Meningkatkan imunitas dapat dilakukan antara lain dengan mengkonsumsi makanan bergizi seimbang. Bentuk kegiatan pengabdian kepada masyarakat ini adalah peningkatan kapasitas masyarakat dengan jenis program pemberian edukasi dan pelatihan pembuatan makanan bergizi seimbang. Mitra dalam program pengabdian kepada masyarakat ini adalah ketua PKK. Partisipasi ketua PKK meliputi pemberian ijin kegiatan dan mengumpulkan masyarakat untuk kegiatan pengabdian kepada masyarakat. Jadwal pelaksanaan kegiatan adalah selama tiga bulan yaitu bulan Agustus-Oktober 2020. Kegiatan ini terlaksana dengan baik, terdapat peningkatan pengetahuan dan keterampilan responden tentang pembuatan makanan bergizi seimbang untuk meningkatkan sistem imun. Sebanyak 87,5% responden memiliki pengetahuan yang baik tentang gizi seimbang, 100% responden dapat membuat makanan bergizi seimbang dan 93,75% responden telah menerapkan pembuatan gizi seimbang pada makanan yang dikonsumsi setiap hari. Saran untuk kegiatan pengabdian masyarakat ini antara lain menambah hari pendampingan sehingga dapat memastikan jika sudah terbentuk kebiasaan dalam penyajian makanan bergizi seimbang dan menambah atau memperluas sasaran karena saat ini sangat penting untuk menyajikan makanan bergizi seimbang.